Power and Subordination in the Novel “Bunga Roos dari Tjikembang”: An Interdiciplinary Approach of Intersectionality, Neuropsychology, and Social Ecology - Thoriqi Firdaus; Raudhatul Jannah (Current Perspectives in Social Sciences)
Literature serves as a mirror reflecting the social, cultural, and psychological dynamics of humanity. Bunga Roos dari Tjikembang, as one of Indonesia’s iconic literary Works, offers a profound narrative to explore these themes. This research aims to provide a comprehensive analysis of the interplay between authority and subordination through the broader lenses of intersectionality, neuropsychology, and social ecology, thereby introducing a more interdisciplinary approach and enriching readers’ understanding of social dynamics in classic literature. This study employs a qualitative approach using textual analysis methods. Data collection is conducted through critical reading of the novel, focusing on text segments that reveal authority relations, social inequalities, and the psychological experiences of characters. Additionally, secondary data, including journal articles, theoretical books, and relevant literature reviews, are utilized to reinforce the analysis and establish a robust theoretical foundation. The findings reveal that the lives of the "Nyai" and the character Marsiti epitomize authority imbalances shaped by gender, ethnicity, and class. This subordination subjects indigenous women to layered oppression, stripping them of autonomy in determining their destinies. A neuropsychological approach highlights the effects of trauma, subjugation, and discrimination on the psychological states of the characters. The social pressures they endure trigger chronic stress, a sense of helplessness, and emotional wounds that ripple through their lives and subsequent generations. The perspective of social ecology illustrates how Marsiti’s subordination as an indigenous woman is constructed through micro-, meso-, and macro-level interactions within colonial society. Despite her marginalization, the symbol of the magnolia flower represents Marsiti’s resilience and emotional contributions, which persist in collective memory as a testament to her resistance against patriarchal norms.